Pharmaceutically active micropollutants: origin, hazards and removal - Gupta, Anuradha; Kumar, Sandeep; Bajpai, Yashi; Chaturvedi, Kavita; Johri, Parul; Tiwari, Rajesh K.; Vivekanand, V.; Trivedi, Mala (Frontiers in Microbiology, 2024)
Pharmaceuticals, recognized for their life-saving potential, have emerged as a concerning class of micropollutants in the environment. Even at minute concentrations, chronic exposure poses a significant threat to ecosystems. Various pharmaceutically active micropollutants (PhAMP), including antibiotics, analgesics, and hormones, have been detected in underground waters, surface waters, seawater, sewage treatment plants, soils, and activated sludges due to the absence of standardized regulations on pharmaceutical discharge. Prolonged exposureof hospital waste and sewage treatment facilities is linked to the presence of antibiotic-resistant bacteria. Conventional water treatment methods prove ineffective, prompting the use of alternative techniques like photolysis, reverse osmosis, UV-degradation, bio-degradation, and nano-filtration. However, commercial implementation faces challenges such as incomplete removal, toxic sludge generation, high costs, and the need for skilled personnel. Research gaps include the need to comprehensively identify and understand various types of pharmaceutically active micropollutants, investigate their long-term ecological impact, develop more sensitive monitoring techniques, and explore integrated treatment approaches. Additionally, there is a gap in understanding the socio-economic implications of pharmaceutical pollution and the efficacy of public awareness campaigns. Future research should delve into alternative strategies like phagotherapy, vaccines, and natural substance substitutes to address the escalating threat of pharmaceutical pollution.